Microcontroller Based Intelligent Volume Measurement Instrument Using Loadcells - , Anand B. A., Kathyayini H S., Debdip Hazare (Archives of Current Research International, 2024)
This paper presents a microcontroller-based weight measurement system designed specifically for liquid agricultural produce. The system addresses the limitations of traditional volumetric methods by leveraging a load cell to convert liquid weight into an electrical signal. This signal is then digitized by an analog-to-digital converter (ADC) for processing by the microcontroller, the brain of the system. The microcontroller performs calculations, controls component operation, and displays weight data on a user-friendly interface. Additionally, a Bluetooth module enables wireless data transmission for further analysis or integration with farm management software. Performance evaluation using eight different liquid products demonstrated the system's functionality and linearity across a range of volumes. Future advancements could focus on incorporating higher-resolution ADCs for enhanced measurement precision and exploring automated calibration methods for improved user experience. Overall, this microcontroller-based system offers a promising alternative for efficient, accurate, and potentially farm-management integrated measurement of liquid agricultural produce.